THEORY OF COMPLEXITY IN A SMALL BRAZILIAN MICROENTERPRISE SITUATED IN THE WESTERN AMAZON - Campos, Waleska Yone Yamakawa Zavatti; Pante, Carolina; Yamanaka, Cassia Toshie; Rosa, Luciana Aparecida Barbieri da; Motke, Francies Diego (Revista GESTO: Revista de Gestão Estratégica de Organizações, 2022)
This work has as general objective to elaborate a study of the application of the principles of the theory of complexity in face of the practices adopted in Brazilian microenterprise located in the Amazon. Therefore, the following specific objectives were listed: (I) to characterize the principles related to the theory of complexity; (II) to identify relationships between complexity and organizational theory through the characteristics of complex management; (III) to identify factors present in the micro enterprise related to complexity. As for the method, the research is descriptive, using quantitative analysis. The questionnaire used was adapted from the study by Ramalho, Locatelli and Silva (2018). Among the results, it is highlighted that the reductionist principle was identified in the company when the individual attitude affected the organizational collectivity. The principle of retroactivity was observed from the high positive consistency of the responses obtained through mutual feedbacks. The principle of recursion was found from the synergy between people and the ability to establish dynamic relationships. The limitations of the study permeate the performance of a quantitative study. Future studies may involve replicating the in-depth research using a qualitative method in public and private organizations of different sizes.